TAŞIMALI İLKÖĞRETİM ÖĞRENCİLERİNİN TAŞIMALI EĞİTİME İLİŞKİN GÖRÜŞLERİ (THE OPINIONS OF BUSSED PRIMARY SCHOOL STUDENTS RELATED TO BUSSED EDUCATION) - İrfan YURDABAKAN; Mustafa TEKTAŞ (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2013)
The purpose of the study is to identify the opinions of students on bussed education, especially the opinions of those who are transported to bussed education schools. In this qualitative study, interviews were used to collect data. 62 students (boys: 38, girls: 24) from one double-session school and one single-session (whole-day) school comprised the sample. The results revealed that owing to the bussed education system, students were happy and felt they were luckier because they could move along their education, they were protected from any harms during their daily trips, they weren’t walking, they didn’t get cold or wet; additionally those students attending and being transported to other schools said they were better nourished because they could have a lunch. The most serious problem voiced by students was waking up early, whereas girls added that they couldn’t join any extracurricular social, cultural and educational activities, they couldn’t find enough seats on buses and they didn’t fancy the behaviours of drivers.